Platelet reactivity inhibition following ticagrelor loading dose in patients undergoing percutaneous coronary intervention for acute coronary syndrome. (27th July 2019) - Laine, Marc; Panagides, Vassili; Frère, Corinne; Cuisset, Thomas; Gouarne, Caroline; Jouve, Bernard; Thuny, Franck; Paganelli, Franck; Alessi, Marie‐Christine; Mancini, Julien; Bonello, Laurent
Abstract: Background: Ticagrelor induces more potent platelet reactivity (PR) inhibition with reduced interindividual variability compared to clopidogrel. Although on‐clopidogrel PR was shown to correlate with ischemia and bleeding events, no study has investigated the relationship between on‐ticagrelor PR and outcome. Objectives: We aimed to evaluate the relationship between on‐ticagrelor PR, assessed by the vasodilator‐stimulated phosphoprotein index (VASP), and thrombotic and bleeding events in patients with acute coronary syndrome (ACS) treated by percutaneous coronary intervention (PCI). Methods: We performed a prospective, multicenter observational study on patients treated with PCI for ACS. The VASP index was used to assess PR after ticagrelor loading dose (LD). The primary endpoint was the link between major adverse cardiovascular events (MACE) and PR. Results: Among the 530 patients with ACS included, 183 (34.5%) were admitted for ST elevation myocardial infarction. We observed high potency and limited interindividual variability after the ticagrelor LD (VASP 19.1% ± 16.6%). At 1 month, 21 (3.8%) MACE and 29 (5.5%) bleedings ≥ 2 according to the Bleedings Academic Research Consortium (BARC) scale were recorded. Neither MACE nor bleeding was associated with PR ( P  = .34 and P  = .78, respectively). However, there was a strong association between PR and the occurrence of definite acute stent thrombosis ( P  = .03). Platelet reactivity was the only factor associated with acute definite stent thrombosis. Conclusion: In patients receiving a ticagrelor LD while undergoing PCI for ACS, PR using the VASP did not predict MACE or bleeding, but it was significantly associated with the occurrence of definite acute stent thrombosis.